Ascetic figure adorned with a sacred Rudraksha Mala - Temples of India Project Team (Jio Institute, 2024)
One of the ascetics is adorned with a sacred rudraksha mala and a rudraksha armband. The rudraksha (dried stones or seeds of the Elaeocarpus ganitrus associated with Shiva iconography) holds special significance as the sacred symbol of Lord Shiva. It means ‘tears of Shiva.’ According to a legend, once when Shiva was performing penance, tears shed from his eyes and he fell to the ground. Eventually, these transformed into seeds that sprouted into a tree. Thus, this visual depiction of a Shaiva ascetic forms a profound association between the devotee and their lord.